Power Quality Analysis on Arc Furnace Capacitor Bank System in Thailand - Bancha Sreewirote; Atthapol Ngaopitakkul (My University, 2020)
Abstract A large arc furnace plant is currently in operation in Thailand has utilize a capacitor bank system to compensate for the reactive power. However, the use of a capacitor bank, the power quality has become a problem in terms of the harmonic current owing to the switching transient that magnifies the current harmonics and causes severe damage to the capacitor bank and other nearby sensitive equipment. In this study, we investigate the power quality issue in terms of harmonics in a steel furnace factory, and its effect when switching the capacitor bank into a system. We perform the study by using data from an arc furnace plant in Phetchaburi province, Thailand for a case study. The results obtained from the power quality measurement after installing a detuning reactor are satisfactory with a significant decrease in the harmonic current. Thus, the proposed approach can be applied to an arc furnace plant in order to ensure the safety and reliability of the plant.
Keywords: Electric arc furnace; Harmonic; Electric arc; Factory (object-oriented programming); Transient (computer programming); Power Quality and Harmonics